Optimalisasi Lahan Kering Untuk Budidaya Bibit Tanaman Kenaf Sebagai Bahan Baku Industri Menuju Kebangkitan Ekonomi Kreatif Desa Suradadi Kabupaten Tegal - Ibnu Muttaqin; Agnes Dwita Susilawati; Wiyanti, Sari (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
Agriculture in the Suradadi area, Tegal Regency, is still traditional and a tradition passed down from generations to generations. The agricultural pattern of farming is due to the experience and teachings of his parents. For agricultural production, only food crops, secondary crops and fruit are used. They grow crops when the rainy season arrives with high rainwater discharge. The problem that occurs in Suradadi village is less than optimal management of agricultural land which has an impact on the low economic life of Suradadi village farmers. And the aim of this PKM activity is to cultivate kenaf plants in Suradadi village to revive the economic life of farmers in Suradadi village, Tegal Regency. The partner of this PKM is the Gema Ripah farmer group, Suradadi village, Tegal Regency. The problems faced are the frequent harvest failures experienced by PKM Partners, the results obtained are not commensurate with the costs incurred by farmers, and the risk of losses is greater. So that the rice fields can be optimized by planting plants that can withstand heat or rain, and can be planted in various types of soil. Optimizing dry land can be carried out for cultivating kenaf seeds as a farming business in the Suradadi village farmer group, Tegal Regency. The results achieved during the assistance and training in kenaf cultivation, up to the age of 14 days, the kenaf plants grew very well, while keeping the soil moist to avoid evaporation and the plants wilting and dying.